Catalyst with high selectivity for anthraquinone hydrogenation, catalyst carrier and preparation method

By designing a five-coordinated γ-alumina powder as a support, anchoring the active metal palladium to form subnano clusters and a single-atom structure, the problem of low selectivity of existing catalysts is solved, and a high selectivity and high efficiency anthraquinone hydrogenation reaction is achieved.

CN119793429APending Publication Date: 2025-04-11TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411879215.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing anthraquinone hydrogenation catalysts have low selectivity in hydrogenation reactions, resulting in the generation of by-products and affect economic and durability.

Method used

By designing a five-coordinated γ-alumina powder as a carrier, the active metal palladium is anchored using the five-coordinated aluminum site to form sub-nano clusters and a single-atom structure, improving the dispersion of the active metal and metal-support interaction.

Benefits of technology

While reducing the amount of metal palladium used, it is achieved to improve the selectivity and hydrogenation efficiency of the anthraquinone hydrogenation reaction and reduce the generation of by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197762000000091
    Figure BDA0005197762000000091
  • Figure BDA0005197762000000101
    Figure BDA0005197762000000101
  • Figure BDA0005197762000000102
    Figure BDA0005197762000000102
Patent Text Reader

Abstract

The invention discloses a high-selectivity anthraquinone hydrogenation catalyst, a catalyst carrier and a preparation method. The preparation method of the catalyst comprises the following steps: preparation of a carrier: 1) mixing aluminum hydroxide sol with C7-C9 high-carbon alcohol / high-carbon organic amine, and aging to obtain aluminum oxide gel powder; 2) mixing the aluminum oxide gel powder with alcohol, and sequentially drying and roasting to obtain gamma-aluminum oxide powder rich in penta-coordination; the preparation method of the catalyst comprises the following steps: a) mixing a hydrochloric acid aqueous solution containing palladium nitrate with pentacoordinate-rich gamma-aluminum oxide powder; and b) sequentially drying, roasting and reducing the gamma-aluminum oxide powder impregnated with palladium nitrate to obtain the catalyst. The prepared aluminum penta-coordination structure carrier effectively captures palladium to form a sub-nanocluster and a monatomic structure, the exposure rate of active metal is improved, the use amount of metal palladium in an anthraquinone hydrogenation catalyst for a fluidized bed is successfully reduced, the hydrogenation efficiency is improved, and generation of by-products is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a catalyst with high selectivity for anthraquinone hydrogenation, a catalyst carrier and a preparation method. Background Art

[0002] Hydrogen peroxide is a green chemical product with strong oxidizing properties. Currently, 98% of hydrogen peroxide products in the world are produced by the anthraquinone method. The core process of the anthraquinone method is the selective hydrogenation reaction, in which 2-ethylanthraquinone is selectively hydrogenated to form 2-ethylhydroanthraquinone. The hydrogenated working solution reacts with high-purity oxygen, and 2-ethylhydroanthraquinone is oxidized to form hydrogen peroxide. However, the hydrogenation process is also accompanied by the formation of by-products. 2-Ethylhydroanthraquinone will undergo a degradation reaction to form 2-ethylanthraquinone. In addition, excessive hydrogenation of the reaction will also form 2-ethyl-octahydro-9,10-anthraquinone. These by-products cannot form hydrogen peroxide. Considering economy and durability, we should improve the selectivity of the hydrogenation reaction to avoid the formation of by-products.

[0003] The commonly used catalyst for anthraquinone hydrogenation is Pd / γ-alumina catalyst. Previous studies have shown that anthraquinone hydrogenation is a fast reaction controlled by mass diffusion. This means that the number of active sites will directly affect the rate of hydrogenation. Therefore, the high dispersion of active metals has a huge advantage for the desorption of semi-hydrogenated products. In addition, the strong interaction between palladium and the carrier also helps to regulate the electron cloud density, and has outstanding characteristics in inhibiting the hydrogenation of the benzene ring. The problem facing anthraquinone hydrogenation catalysts now is to improve the selectivity and hydrogenation efficiency of the catalyst, which means that research can be conducted from the perspective of improving the dispersion and electronic state of metal palladium.

[0004] For γ-alumina, alumina with unsaturated coordination centers has also been shown to fix active components. Unsaturated five-coordinated aluminum ions have an important influence on stabilizing active metal species, optimizing carrier acid-base sites, stabilizing biocatalytic processes, enzyme immobilization, and synthesizing chiral compounds. The five-coordinated aluminum sites serve as anchoring sites to effectively disperse and stabilize active metals through strong metal-carrier interactions. Therefore, compared with the methods of using atomic layer deposition and using bimetallic coordination of active metal electronic properties, the synthesis of γ-alumina carriers with rich aluminum five-coordinate centers can bring about high dispersion of active metals and strong metal-carrier interaction characteristics, which can show more excellent catalytic performance and stability in anthraquinone hydrogenation.

[0005] The exposure of the alumina crystal surface has a mapping relationship with the coordination environment and the exposure of the terminal hydroxyl groups. DFT calculations reveal that the (100) surface of γ-alumina has more terminal hydroxyl groups than the (110) surface, allowing active metals to be anchored as single atoms through the terminal hydroxyl groups. When there are not enough terminal hydroxyl groups to anchor the active metals, they tend to aggregate to form large metal particles. Therefore, the type of crystal surface exposed on γ-alumina significantly affects the content of terminal hydroxyl groups, thereby affecting the dispersion of the metal. When Pd is loaded on the γ-alumina crystal surface as a catalyst, it is found that on the γ-alumina (100) surface, palladium mainly exists in the form of single atoms. In contrast, on the γ-alumina (111) surface, palladium easily aggregates to form palladium clusters. Based on the "terminal hydroxyl anchoring mechanism", by designing the carrier crystal surface structure to achieve the dispersion and anchoring of palladium metal, efficient new catalysts suitable for the preparation of single-atom catalysts and sub-nano cluster-level catalysts can be developed.

[0006] The prior art has disclosed the following implementation schemes:

[0007] Bimetallic catalysts: By doping with a second metal, the electron transfer between the second metal and Pd is constructed, the interaction between the active metal and alumina is enhanced, and the anchoring effect of the palladium species is strengthened. Bimetallic catalysts improve the dispersibility of Pd and the catalytic activity and durability of anthraquinone hydrogenation. Not only can the addition of a second metal change the metal-support interaction in the catalyst, but the metal oxide can also enhance the anchoring effect of the metal Pd component.

[0008] Atomic layer deposition: Atomic layer deposition is a precise metal deposition technology used to make catalysts. It deposits atoms layer by layer on the substrate by alternately introducing two precursor gases, achieving precise control of thickness and composition. Atomic layer deposition has the advantages of uniform deposition and low-temperature operation, and is suitable for the preparation of supported catalysts and core-shell structures.

[0009] However, the above two methods also face common disadvantages, the most important of which are high cost and complexity. Atomic layer deposition technology requires precise control of reaction conditions and expensive equipment, and the synthesis of bimetallic catalysts also requires sophisticated strategies; in addition, the preparation process is long, which limits the ability of large-scale rapid production; the limitation of precursors and the scope of application also limit the widespread use of the technology; at the same time, uniformity and stability issues, as well as the limitations of the technology in processing complex-shaped substrates, are all challenges that these methods need to overcome in practical applications.

[0010] Therefore, from the perspective of the carrier, by designing the coordination structure and crystal surface structure of the carrier to achieve the construction of five-coordinated aluminum sites, and using five-coordinated alumina to anchor the active metal, it has the huge advantages of high efficiency, indirectness and low cost. Summary of the invention

[0011] In view of the defects of the prior art, the present invention provides a five-coordinated γ-alumina powder and a catalyst for anthraquinone hydrogenation with high selectivity prepared based on the carrier. The present invention takes advantage of the rich hydroxyl functional groups of high-carbon alcohols and directionally adsorbs them in the hydroxyl sites of boehmite primary particles in aluminum hydroxide sol. After calcination, the hydroxyl sites are protected, oxygen vacancies are formed, and a carrier with a rich aluminum five-coordinate structure is constructed. Palladium is effectively captured to form sub-nano clusters and single-atom structures, and the exposure rate of active metals is increased, successfully achieving the reduction of the amount of metal palladium used in the anthraquinone hydrogenation catalyst for fluidized bed, while improving the hydrogenation efficiency and reducing the generation of by-products.

[0012] In order to achieve the above object, the present invention adopts the following technical solution:

[0013] In a first aspect, the present invention provides a method for preparing pentacoordinate-rich γ-alumina powder.

[0014] The method for preparing penta-coordinate-rich γ-alumina powder provided by the present invention comprises the following steps:

[0015] 1) mixing aluminum hydroxide sol with C7-C9 high carbon alcohol / high carbon organic amine, and aging to obtain alumina gel powder;

[0016] 2) After mixing the alumina gel powder with alcohol, drying and calcining are performed in sequence to obtain penta-coordinated γ-alumina powder.

[0017] In step 1) of the above method, the purity of the aluminum hydroxide sol is greater than 99%, preferably greater than 99.5%; the solid content of the aluminum hydroxide sol is preferably 5-25wt%, and optimally 20wt%.

[0018] In step 1) of the above method, the higher carbon alcohol / high carbon organic amine is at least one of the following: n-heptanol, n-octanol, n-nonanol, n-heptylamine, n-octylamine and n-nonylamine;

[0019] In step 1) of the above method, the amount of the higher carbon alcohol / high carbon organic amine added is preferably 5-10 times the mass of the aluminum hydroxide sol, and optimally 8 times.

[0020] In step 1) of the above method, the aging is carried out under stirring conditions. The stirring rate is preferably 800-1500 rpm.

[0021] According to some embodiments of the present invention, the aging stirring rate is 1000 rpm.

[0022] In step 1) of the above method, the aging temperature is preferably 80-95 degrees Celsius; the aging time is preferably 100-200 minutes.

[0023] According to some embodiments of the present invention, the aging temperature is 90 degrees Celsius; and the aging time is 180 minutes.

[0024] In step 1) of the above method, the molecular structure of the high-carbon alcohol / high-carbon organic amine has a hydroxyl-philic functional group, which can hydrogen bond with the hydroxyl bonds of the boehmite primary particles, thereby adsorbing on the surface of the boehmite primary particles, occupying oxygen vacancies and protecting the five-coordinated sites of the boehmite primary particles, thereby protecting the oxygen vacancies and the existence of five-coordinated aluminum hydroxyls in the subsequent calcination process.

[0025] In step 2) of the above method, by mixing the alumina gel powder with the alcohol solution, and then drying and calcining, a γ-alumina powder rich in penta-coordination can be obtained. According to an embodiment of the present invention, the alumina gel powder is first immersed in an alcohol solution, and then the immersed alumina gel powder is dried. During the volatilization process of the alcohol solution, the residual solvent in the alumina gel powder can be induced to be stably removed. Finally, the dried alumina gel powder is calcined to dehydrate the AlOOH and transform it into an Al-O-Al structure, so that a γ-alumina powder rich in penta-coordination can be obtained.

[0026] In step 2) of the above method, the mass ratio of the alumina gel powder to the alcohol is preferably 1:(10-20).

[0027] According to some embodiments of the present invention, the mass ratio of the alumina gel powder to the alcohol may be 1:10, 1:15, 1:20, etc.

[0028] In step 2) of the above method, the type of alcohol is not particularly limited, and those skilled in the art can flexibly select it according to actual conditions. According to some embodiments of the present invention, the number of carbon atoms of the alcohol can be 2 or 3, which can promote the appropriate mutual solubility and diffusivity between alcohol and water, so that the alcohol can effectively diffuse into the interior of the alumina gel powder, which is conducive to removing the remaining solvent in the alumina gel powder during drying. In some specific embodiments of the present invention, the alcohol includes at least one of ethanol or propanol.

[0029] In step 2) of the above method, the mixing time is preferably 5-10 minutes. Thus, the alcohol and the alumina gel powder can be mixed evenly, so that the alcohol can penetrate into the interior of the alumina gel powder, which is conducive to removing the remaining solvent in the alumina gel powder during drying.

[0030] According to some embodiments of the present invention, the mixing time may be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.

[0031] In step 2) of the above method, the drying temperature is preferably 20°C-40°C.

[0032] In step 2) of the above method, the drying time is preferably 8h-20h.

[0033] According to some embodiments of the present invention, the drying temperature may be 20° C., 25° C., 30° C., 35° C., 40° C., etc. The drying time may be 8 h, 10 h, 12 h, 15 h, 20 h, etc.

[0034] In step 2) of the above method, the calcination temperature is 550° C.-700° C. Thus, γ-alumina powder with uniform crystal phase can be obtained.

[0035] In step 2) of the above method, the calcination time is 3h-6h, so as to obtain γ-alumina powder with uniform crystal phase.

[0036] According to some embodiments of the present invention, the calcination temperature may be 550°C, 600°C, 650°C, 700°C, etc., and the calcination time may be 3h, 4h, 5h, 6h, etc.

[0037] In a second aspect, the present invention provides a penta-coordinate-rich γ-alumina powder prepared according to the first aspect.

[0038] In the penta-coordinated γ-alumina powder, the proportion of penta-coordinated hydroxyl groups in all hydroxyl groups of the γ-alumina is between 0.1 and 0.15.

[0039] In a third aspect, the present invention provides an application of the penta-coordinate-rich γ-alumina powder described in the second aspect.

[0040] The application is the application of the invention in preparing an alumina carrier for a fluidized bed or in preparing a catalyst for highly selective anthraquinone hydrogenation.

[0041] In a fourth aspect, the present invention provides a method for preparing a Pd-alumina catalyst for a fluidized bed.

[0042] The preparation method of the Pd-alumina catalyst for a fluidized bed provided by the present invention comprises the following steps:

[0043] a) mixing an aqueous hydrochloric acid solution containing palladium nitrate with the penta-coordinated γ-alumina powder to obtain γ-alumina powder impregnated with palladium nitrate;

[0044] b) drying, calcining and reducing the γ-alumina powder impregnated with palladium nitrate in sequence to obtain the Pd-alumina catalyst for the fluidized bed.

[0045] In step a) of the above method, the preparation method of the hydrochloric acid aqueous solution containing palladium nitrate is: adding hydrated palladium nitrate to a hydrochloric acid aqueous solution with a pH of 3-5 at room temperature; in order to accurately obtain the precious metal loading, it is necessary to calculate according to the five-coordinate-rich γ-alumina powder used. The mass ratio of the hydrated palladium nitrate to the five-coordinate-rich γ-alumina powder used is preferably 2.16:100-0.216:100, and the corresponding hydrated palladium nitrate is dissolved in a hydrochloric acid aqueous solution with a pH of 3-5. The corresponding precious metal loading of the finally prepared Pd-alumina catalyst is 1%-0.1%.

[0046] In step a) of the above method, the mass ratio of the penta-coordinated γ-alumina powder to the aqueous hydrochloric acid solution containing palladium nitrate is 1:1. Therefore, the mass ratio of the hydrated palladium nitrate to the aqueous hydrochloric acid solution with a pH of 3-5 is preferably 2.16:100-0.216:100. When the mass ratio of the penta-coordinated γ-alumina powder to the aqueous hydrochloric acid solution containing palladium nitrate exceeds 1:1, insufficient metal dispersion will result. A ratio of less than 1:1 will result in the inability of the metal salt to completely enter the penta-coordinated γ-alumina powder.

[0047] In step a) of the above method, preferably, the hydrochloric acid aqueous solution containing palladium nitrate is added dropwise to the penta-coordinated γ-alumina powder. The rate of the dropwise addition is preferably 5-10 ml / min, and the optimal is 8 ml / min. After the dropwise addition is completed, it is kept at room temperature for 30-120 minutes, and the optimal is 60 minutes, so that the penta-coordinated γ-alumina powder can completely absorb the added hydrochloric acid aqueous solution containing palladium nitrate.

[0048] In step a) of the above method, by optimizing the impregnation process of pentacoordinate-rich γ-alumina powder, oxygen vacancies and pentacoordinate hydroxyl sites are fully utilized, and Pd is precisely captured based on the principle of "terminal hydroxyl anchoring mechanism".

[0049] In step b) of the above method, the drying temperature is preferably 120-240 minutes, most preferably 180 minutes. The drying temperature is 80-120°C, most preferably 100°C.

[0050] According to some embodiments of the present invention, the drying temperature may be 80° C., 90° C., 100° C., 110° C., 120° C., etc. The drying time may be 120 minutes, 150 minutes, 180 minutes, 210 minutes, etc.

[0051] In step b) of the above method, the calcination is carried out after naturally cooling to room temperature after drying. The calcination temperature is preferably 300-500°C, and most preferably 400°C. The heating rate is 2-10 degrees Celsius / minute, and preferably 5 degrees Celsius / minute. After reaching the calcination temperature, the temperature is maintained for 2-4 hours, and most preferably 3 hours.

[0052] According to some embodiments of the present invention, the calcination temperature may be 300° C., 400° C., 500° C., etc. The calcination time may be 2 hours, 3 hours, 4 hours, etc.

[0053] In step b) of the above method, the reduction is carried out after naturally cooling to room temperature after calcination. The atmosphere used for the reduction is preferably a 10% hydrogen / argon mixed gas, and the mixed gas flow rate is preferably 100-400 ml / min, and the optimal is 200 ml / min. The reduction temperature is preferably 300-400 degrees Celsius, and the optimal is 350 degrees Celsius. The heating rate is 2-10 degrees Celsius / minute, and preferably 5 degrees Celsius / minute. The reduction time is preferably 2-4 hours, and the optimal is 3 hours. Then naturally cool to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0054] According to some embodiments of the present invention, the mixed gas flow rate used for the reduction may be 100 ml / min, 200 ml / min, 300 ml / min or 400 ml / min, etc. The reduction temperature may be 300° C., 320° C., 350° C., 380° C., 400° C., etc. The reduction time may be 2 hours, 3 hours, 4 hours, etc.

[0055] In a fifth aspect, the present invention provides a Pd-alumina catalyst for a fluidized bed prepared in the fourth aspect.

[0056] The catalyst can control the Pd content to a minimum of 0.1%, thereby realizing the preparation of a Pd-alumina catalyst with ultra-low noble metal loading.

[0057] In a sixth aspect, the present invention provides the use of the Pd-alumina catalyst for a fluidized bed as described in the fifth aspect.

[0058] The application is the application of the compound as a catalyst for highly selective anthraquinone hydrogenation, or the application of the compound in preparing a catalyst for highly selective anthraquinone hydrogenation.

[0059] In a seventh aspect, the present invention provides a method for producing hydrogen peroxide by catalytic hydrogenation of anthraquinone.

[0060] The method comprises using the above-mentioned fluidized bed to catalyze the anthraquinone hydrogenation reaction using a Pd-alumina catalyst.

[0061] Furthermore, the method comprises the following steps: mixing the anthraquinone working solution with the fluidized bed Pd-alumina catalyst to carry out anthraquinone catalytic hydrogenation reaction; and then oxidizing the hydrogenated liquid obtained after the reaction to obtain hydrogen peroxide.

[0062] The concentration of anthraquinone in the anthraquinone working solution is 80-120 g / L, specifically 100 g / L;

[0063] The anthraquinone is selected from at least one of the following: 2-ethylanthraquinone, amylanthraquinone;

[0064] The solvent in the anthraquinone working solution includes heavy aromatic hydrocarbons and trioctyl phosphate, and the volume ratio of the heavy aromatic hydrocarbons to trioctyl phosphate can be (2-4):1, specifically 3:1.

[0065] The ratio of the anthraquinone working solution to the catalyst is (10-40) ml:0.2 g, specifically 20 ml:0.2 g.

[0066] The reaction conditions of the anthraquinone catalytic hydrogenation reaction are: reaction temperature 25-65° C., use of high-purity hydrogen as a raw material, reaction pressure 0.1-0.4 MPa, specifically 0.3 MPa; reaction time 0.25-1 hour, stirring rate 500-1200 rpm.

[0067] Preferably, the anthraquinone catalytic hydrogenation reaction is carried out in a fluidized bed reactor.

[0068] At present, the technologies for improving metal dispersion and enhancing metal-support interaction to reduce the amount of precious metals mainly include atomic layer deposition and construction of bimetallic catalysts. However, these technologies generally have problems such as high cost and complexity. For example, atomic layer deposition requires precise reaction condition control and high equipment cost, and the synthesis of bimetallic catalysts also requires sophisticated strategies. Based on these challenges, from the perspective of the support, by designing the coordination structure and crystal surface structure of the support, constructing penta-coordinated aluminum sites, these special sites can be used to anchor active metals. The construction of penta-coordinated aluminum sites has the following advantages: 1) Improve metal dispersion: Penta-coordinated aluminum sites provide more anchoring sites, which help to disperse active metals more evenly, thereby increasing the active surface area of ​​the catalyst. 2) Enhance metal-support interaction: Penta-coordinated aluminum sites may have higher activity and can form stronger chemical bonds with active metals, thereby enhancing the interaction between metal and support and improving the stability of the catalyst. 3) Reduce the amount of precious metals: Due to the improvement of metal dispersion and the enhancement of metal-support interaction, the amount of precious metals can be reduced without sacrificing the performance of the catalyst. 4) Simplify the preparation process: Compared with the complex synthesis strategies of atomic layer deposition and bimetallic catalysts, anchoring metals through support design may be simpler and more direct. 5) Cost-effectiveness: Compared with expensive equipment and delicate operations, constructing pentacoordinated aluminum sites through support modification may be more cost-effective. 6) Improve adaptability: The design of pentacoordinated aluminum sites may be more flexible and can adapt to substrates of different shapes and sizes, thereby expanding the scope of application. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 The solid nuclear magnetic resonance images of the γ-alumina powder prepared in Examples 1-2 and Comparative Examples 1-4;

[0070] Figure 2 This is a spherical aberration electron microscope image of the catalyst prepared in Example 1;

[0071] Figure 3 This is the spherical aberration electron microscope image of the catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION

[0072] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0073] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0074] The aluminum hydroxide sol with a purity of 99% and a solid content of 15 wt % used in the following examples was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., with the product catalog number: VK-L10A.

[0075] Example 1

[0076] 1) Weigh 1000 g of aluminum hydroxide sol with a purity of 99% and a solid content of 15 wt %, pour 8000 g of n-octanol into the sol, place in a 90°C water bath, age for 180 minutes at a speed of 1000 rpm, then filter out excess n-octanol to obtain alumina gel powder.

[0077] 2) Immerse 200 g of alumina gel powder in 2000 mL of ethanol and slowly stir the alumina gel powder in the ethanol for 10 min. Place the soaked alumina gel powder in an air-dried state at 25 °C for 12 h. Then, calcine the dried alumina gel powder at 600 °C for 6 h to obtain a penta-coordinated γ-alumina powder.

[0078] 3) 0.216 g of hydrated palladium nitrate was dissolved in 100 g of a hydrochloric acid solution with a pH of 4. 100 g of the penta-coordinated γ-alumina powder obtained in step 2) was taken and the hydrochloric acid solution containing palladium nitrate was added dropwise into the 100 g of alumina powder at a rate of 8 ml / min. After the addition was completed, the mixture was kept at room temperature for 60 minutes to allow the microspheres to completely absorb the hydrochloric acid solution. The palladium content of the impregnated catalyst was 0.1%.

[0079] 4) Dry the impregnated catalyst at 100°C for 180 minutes. After drying, cool naturally to room temperature and then calcine. Heat to 400°C at a rate of 5°C / min and calcine for 3 hours. Then cool naturally to room temperature. Perform reduction. Purge the impregnated catalyst with 200 ml / min of 10% hydrogen / argon mixed gas, heat to 350°C at a heating rate of 5 degrees Celsius / min, and maintain the temperature for 3 hours. Then cool naturally to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0080] Example 2

[0081] 1) Weigh 1000 g of aluminum hydroxide sol with a purity of 99% and a solid content of 15 wt %, pour 8000 g of n-octylamine into the sol, place in a 90°C water bath, age for 180 minutes at a speed of 1000 rpm, then filter out excess n-octanol to obtain alumina gel powder.

[0082] 2) Immerse 200 g of alumina gel powder in 2000 mL of ethanol and slowly stir the microspheres in the ethanol for 10 min. Place the soaked alumina gel microspheres in an air-dried state at 25 °C for 12 h. Then, calcine the dried alumina gel microspheres at 600 °C for 6 h to obtain penta-coordinated γ-alumina powder.

[0083] 3) Dissolve 0.216 g of hydrated palladium nitrate in 100 g of a hydrochloric acid solution with a pH of 4. Take 100 g of alumina powder rich in penta-coordinated γ-position obtained in step 2), and add the hydrochloric acid solution containing palladium nitrate dropwise into 100 g of alumina powder at a rate of 8 ml / min. After the addition is completed, keep it at room temperature for 60 minutes to allow the microspheres to completely absorb the hydrochloric acid solution. The palladium content of the impregnated catalyst is 0.1%.

[0084] 4) Dry the impregnated catalyst at 100°C for 180 minutes. After drying, cool naturally to room temperature and then calcine. Heat to 400°C at a rate of 5°C / min and calcine for 3 hours. Then cool naturally to room temperature. Perform reduction. Purge the impregnated catalyst with 200 ml / min of 10% hydrogen / argon mixed gas, heat to 350°C at a heating rate of 5 degrees Celsius / min, and maintain the temperature for 3 hours. Then cool naturally to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0085] Comparative Example 1

[0086] Alumina carrier obtained by commercial spray drying was purchased, and 120-60 micron alumina powder was selected through sieving. 0.216 g of hydrated palladium nitrate was dissolved in 100 g of hydrochloric acid solution with pH=4, 100 g of alumina powder was taken, and the hydrochloric acid solution containing palladium nitrate was dripped into 100 g of alumina powder at a rate of 8 ml / min. After the dripping was completed, it was kept at room temperature for 60 minutes so that the microspheres completely absorbed the hydrochloric acid solution. The palladium content of the impregnated catalyst was 0.1%.

[0087] The impregnated catalyst was dried at 100°C for 180 minutes. After drying, it was naturally cooled to room temperature and then calcined. The temperature was raised to 400°C at a rate of 5°C / min and calcined for 3 hours. Then it was naturally cooled to room temperature. Reduction was performed. The impregnated catalyst was purged with 200 ml / min of 10% hydrogen / argon mixed gas, and the temperature was raised to 350°C at a heating rate of 5 degrees Celsius / min, and the temperature was maintained for 3 hours. Then it was naturally cooled to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0088] Comparative Example 2

[0089] Alumina carrier obtained by commercial oil-ammonia column method was purchased, crushed and sieved to select 120-60 micron alumina powder. 0.216g of hydrated palladium nitrate was dissolved in 100g of hydrochloric acid solution with pH=4, and 100g of alumina powder was taken, and the hydrochloric acid solution containing palladium nitrate was added dropwise to 100g of alumina powder at a rate of 8ml / min. After the addition was completed, it was kept at room temperature for 60 minutes to allow the microspheres to completely absorb the hydrochloric acid solution. The palladium content of the impregnated catalyst was 0.1%.

[0090] The impregnated catalyst was dried at 100°C for 180 minutes. After drying, it was naturally cooled to room temperature and then calcined. The temperature was raised to 400°C at a rate of 5°C / min and calcined for 3 hours. Then it was naturally cooled to room temperature. Reduction was performed. The impregnated catalyst was purged with 200 ml / min of 10% hydrogen / argon mixed gas, and the temperature was raised to 350°C at a heating rate of 5 degrees Celsius / min, and the temperature was maintained for 3 hours. Then it was naturally cooled to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0091] Comparative Example 3

[0092] Purchase alumina carrier obtained by commercial drop ball method, crush and sieve to select 120-60 micron alumina powder. Dissolve 0.216g hydrated palladium nitrate in 100g hydrochloric acid aqueous solution with pH=4, take 100g alumina powder, add the hydrochloric acid aqueous solution containing palladium nitrate to 100g alumina powder at a rate of 8ml / min, and keep it at room temperature for 60 minutes after the addition is completed, so that the microspheres completely absorb the hydrochloric acid aqueous solution, and the palladium content of the impregnated catalyst is 0.1%. Dry the impregnated catalyst at 100°C for 180 minutes. After drying, cool it naturally to room temperature and then calcine it. Heat to 400°C at a rate of 5°C / min and calcine for 3 hours. Then cool it naturally to room temperature. Reduce it. Use 200 ml / min of 10% hydrogen / argon mixed gas to purge the impregnated catalyst, heat it to 350°C at a heating rate of 5 degrees Celsius / min, and keep this temperature for 3 hours. The mixture was then cooled naturally to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0093] Comparative Example 4

[0094] Alumina carrier obtained by commercial rolling ball method was purchased, crushed and sieved to select 120-60 micron alumina powder. 0.216g of hydrated palladium nitrate was dissolved in 100g of hydrochloric acid solution with pH=4, and 100g of alumina powder was taken, and the hydrochloric acid solution containing palladium nitrate was added dropwise into 100g of alumina powder at a rate of 8ml / min. After the addition was completed, it was kept at room temperature for 60 minutes to allow the microspheres to completely absorb the hydrochloric acid solution. The palladium content of the impregnated catalyst was 0.1%.

[0095] The impregnated catalyst was dried at 100°C for 180 minutes. After drying, it was naturally cooled to room temperature and then calcined. The temperature was raised to 400°C at a rate of 5°C / min and calcined for 3 hours. Then it was naturally cooled to room temperature. Reduction was performed. The impregnated catalyst was purged with 200 ml / min of 10% hydrogen / argon mixed gas, and the temperature was raised to 350°C at a heating rate of 5 degrees Celsius / min, and the temperature was maintained for 3 hours. Then it was naturally cooled to room temperature to obtain a Pd-alumina catalyst for anthraquinone hydrogenation fluidized bed.

[0096] The alumina powders of Examples 3-7 are the same as those of Example 2 except for different experimental parameters (see Table 1).

[0097] The experimental parameters of Examples 1-7 and Comparative Examples 1-4 of the present application are shown in Table 1.

[0098] Table 1 Experimental parameters of Examples 1-8 and Comparative Examples 1-4

[0099]

[0100] The solid NMR spectra of the γ-alumina powders prepared in Examples 1-2 and Comparative Examples 1-4 are as follows: Figure 1 As shown in the figure, the pentacoordinate-rich prepared in Example 1-2 has more abundant pentacoordinates.

[0101] The spherical aberration electron microscope image of the catalyst prepared in Example 1 is as follows Figure 2 As shown in the figure, the γ-alumina with rich five-coordination can make Pd more strongly dispersed and provide strong metal-support interaction based on the "terminal hydroxyl anchoring" effect.

[0102] The spherical aberration electron microscope image of the catalyst prepared in Comparative Example 1 is as follows Figure 3 As shown in the figure, the lack of rich five-coordinated γ-alumina makes Pd easily agglomerated and forms large particles.

[0103] The catalyst prepared in the following example is evaluated by anthraquinone hydrogenation hydrogenation efficiency: a 50mL small autoclave reactor is used to simulate the fluidized bed process for activity evaluation. The evaluation conditions are: reaction temperature 25-65°C, high-purity hydrogen is used as raw material, and the reaction pressure is 0.3MPa. The reaction time is 0.25-1 hour, and the stirring rate is 1000 rpm. Working liquid composition: 2-ethylanthraquinone 100g / L, heavy aromatics and trioctyl phosphate volume ratio 3:1. 20ml of working liquid and 0.2g of catalyst are loaded into an autoclave and reacted at the selected reaction temperature, reaction pressure, reaction time and stirring rate. The hydrogenated liquid after the reaction is oxidized at 50°C for 30min, extracted four times with pure water, and the content of hydrogen peroxide is analyzed. The hydrogen peroxide content is detected by potassium permanganate titration. Finally, the hydrogenation efficiency is calculated. 2-Ethylanthraquinone is analyzed and detected by high performance liquid chromatography.

[0104] The calculation formula of hydrogen efficiency is:

[0105]

[0106] Among them are hydrogen efficiency (g / L), potassium permanganate concentration (mol / L), potassium permanganate usage volume (L), hydrogen peroxide relative molecular mass is 34 (g / mol), and oxidized working solution volume (L).

[0107] The formula for calculating hydrogenation efficiency is:

[0108]

[0109] The data include hydrogenation efficiency (g hydrogen peroxide / g palladium / h), hydrogen efficiency (g / L), volume of working solution used in the reaction (L), catalyst mass (g), mass fraction of palladium (%), and reaction time (h).

[0110] The calculation formula for the proportion of 2-ethylanthraquinone and by-products is:

[0111]

[0112] By-product ratio (%) = 100% - (2-ethylanthraquinone ratio)

[0113] The concentrations (g / L) of 2-ethylanthraquinone before and after the reaction were analyzed by high performance liquid chromatography. During the reaction, 2-ethylanthraquinone will first be hydrogenated to form 2-ethylhydroanthraquinone, and then oxidized back to 2-ethylanthraquinone. The by-products are over-hydrogenated products and will not be oxidized back to 2-ethylanthraquinone. Therefore, the proportion of by-products in the reaction process can be obtained based on the proportion of 2-ethylanthraquinone after oxidation.

[0114] In the evaluation reactions, except for the catalyst type, reaction temperature and reaction time, other reaction conditions were the same.

[0115] The experimental parameters and results of this reaction are shown in Table 2.

[0116] Table 2 Experimental parameters and reaction results of the evaluation reaction

[0117]

[0118] It can be seen from Table 2 that the catalyst prepared with the γ-alumina powder with rich penta-coordination provided by the present invention has a higher hydrogenation efficiency and a lower loading ratio (at 25° C.).

[0119] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.

Claims

1. A method for preparing penta-coordinated γ-alumina powder, comprising the following steps: 1) mixing aluminum hydroxide sol with C7-C9 high carbon alcohol and / or high carbon organic amine, and aging to obtain aluminum oxide gel powder; 2) After mixing the alumina gel powder with alcohol, drying and calcining are performed in sequence to obtain penta-coordinated γ-alumina powder.

2. The preparation method according to claim 1, characterized in that: In the step 1), the purity of the aluminum hydroxide sol is greater than 99%; the solid content of the aluminum hydroxide sol is 5-25wt%; And / or, in the step 1), the higher carbon alcohol and / or higher carbon organic amine is at least one of the following: n-heptanol, n-octanol, n-nonanol, n-heptylamine, n-octylamine and n-nonylamine; And / or, in the step 1), the amount of the high carbon alcohol and / or high carbon organic amine added is 5-10 times the mass of the aluminum hydroxide sol.

3. The preparation method according to claim 1 or 2, characterized in that: In the step 1), the aging is carried out under stirring conditions; the stirring rate is 800-1500 rpm; And / or, in the step 1), the aging temperature is 80-95 degrees Celsius; the aging time is 100-200 minutes.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 4), the mass ratio of the alumina gel powder to the alcohol is 1:(10-20); and / or, the alcohol has 2 to 4 carbon atoms; And / or, the mixing time is 5 min-10 min; And / or, the drying temperature is 20°C-40°C; And / or, the drying time is 8h-20h; And / or, the calcination temperature is 550°C-700°C; And / or, the calcination time is 3h-6h.

5. The pentacoordinate-rich γ-alumina powder prepared according to the method according to any one of claims 1 to 4.

6. A method for preparing a Pd-alumina catalyst for a fluidized bed, comprising the following steps: a) mixing an aqueous hydrochloric acid solution containing palladium nitrate with the pentacoordinate-rich γ-alumina powder according to claim 5 to obtain a γ-alumina powder impregnated with palladium nitrate; b) drying, calcining and reducing the γ-alumina powder impregnated with palladium nitrate in sequence to obtain the Pd-alumina catalyst for the fluidized bed.

7. The preparation method according to claim 6, characterized in that: In the step a), the preparation method of the hydrochloric acid aqueous solution containing palladium nitrate is: adding hydrated palladium nitrate to a hydrochloric acid aqueous solution with a pH of 3-5 at room temperature; the mass ratio of the hydrated palladium nitrate to the hydrochloric acid aqueous solution with a pH of 3-5 is 2.16:100-0.216:100; In the step a), the mass ratio of hydrated palladium nitrate to penta-coordinated γ-alumina powder in the hydrochloric acid aqueous solution containing palladium nitrate is 2.16:100-0.216:100; In the step a), the mass ratio of the penta-coordinated γ-alumina powder to the hydrochloric acid aqueous solution containing palladium nitrate is 1:1; And / or, in the step a), the mixing is to add the hydrochloric acid aqueous solution containing palladium nitrate dropwise into the penta-coordinated γ-alumina powder; the dropping rate is preferably 5-10 ml / min, and the mixture is kept at room temperature for 30-120 minutes after the dropping is completed.

8. The preparation method according to claim 6 or 7, characterized in that: In the step b), the drying time is 120-240 minutes and the drying temperature is 80-120°C; And / or, in the step b), the calcination temperature is 300-500°C, the heating rate is 2-10°C / min, and after reaching the calcination temperature, the temperature is maintained for 2-4 hours; And / or, in the step b), the reduction atmosphere is 10% hydrogen / argon mixed gas, the flow rate of the mixed gas is 100-400 ml / min; the reduction temperature is 300-400 degrees Celsius, the heating rate is 2-10 degrees Celsius / min; the reduction time is 2-4 hours.

9. A Pd-alumina catalyst for a fluidized bed prepared according to the method of any one of claims 6 to 8.

10. A method for producing hydrogen peroxide by catalytic hydrogenation of anthraquinone, comprising: The anthraquinone hydrogenation reaction is catalyzed by the Pd-alumina catalyst for fluidized bed according to claim 9.

11. The method according to claim 10, characterized in that: The method comprises the following steps: mixing the anthraquinone working solution with the fluidized bed Pd-alumina catalyst to carry out anthraquinone catalytic hydrogenation reaction; and then oxidizing the hydrogenated liquid obtained after the reaction to obtain hydrogen peroxide; Preferably, the concentration of anthraquinone in the anthraquinone working solution is 80-120 g / L; Preferably, the anthraquinone is selected from at least one of the following: 2-ethylanthraquinone, amylanthraquinone; Preferably, the solvent in the anthraquinone working solution comprises heavy aromatic hydrocarbons and trioctyl phosphate, and the volume ratio of the heavy aromatic hydrocarbons to trioctyl phosphate is (2-4):1; Preferably, the ratio of the anthraquinone working solution to the catalyst is (10-40) ml: 0.2 g; Preferably, the reaction conditions of the anthraquinone catalytic hydrogenation reaction are: reaction temperature 25-65° C., use of high-purity hydrogen as a raw material, reaction pressure 0.1-0.4 MPa; reaction time 0.25-1 hour, stirring rate 500-1200 rpm; Preferably, the anthraquinone catalytic hydrogenation reaction is carried out in a fluidized bed reactor.